Preeklampsia-Eklampsia sebagai Faktor Risiko Kematian Maternal di RSUD Ulin Banjarmasin - Aditya, Renhny; Tobing, Samuel Lumban; Elyani, Rezeki Ananda; Heriyani, Farida (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Preeclampsia-eclampsia is the second highest risk factor of maternal mortality after hemorrhage. This research aimed to analyze preeclampsia-eclampsia as a risk factor of maternal mortality in The General Hospital of Ulin Banjarmasin. Methods: This research used observational analytic method with case control approach. Data were taken from registration book in VK Bersalin (Delivery Room) of The General Hospital of Ulin Banjarmasin and patient’s medical record. The sample of this research was 30 samples for each case and control group which used simple random sampling. Results: In maternal mortality group, 50% is caused by preeclampsia-eclampsia and 50% is caused by non preeclampsia-eclampsia. In non maternal mortality group, 10% is caused by peeclampsia-eclampsia and 90% is caused by non preeclampsia-eclampsia. Chi-square test shows a significant result ('=0,001) and Odds Ratio (OR=9,000). Conclusions: Preeclampsia-eclampsia has 9 times higher risk of maternal mortality than non preeclampsia-eclampsia.